Epidural Neostigmine and Clonidine Improves the Quality of Combined Spinal-Epidural Analgesia in Labor. Issue 2 (June 2015) - Boogmans, T.; Vertommen, J.; Valkenborgh, T.; Devroe, S.; Roofthooft, E.; Van de Velde, M.
<x xml:space="preserve">Abstract</x> (Eur J Anaesthesiol. 2014;31(4):190–196)